The extent of financial disclosure and its determinants in an emerging capital market: the case of Egypt. (19th June 2006) - Hassan, Omaima A.G.; Giorgioni, Gianluigi; Romilly, Peter
This paper uses panel data analysis to investigate the extent and determinants of disclosure levels of non-financial companies quoted on the Egyptian Stock Exchange. It distinguishes between private sector companies and public business sector companies in terms of company characteristics and disclosure practice. Results show gradual increases in disclosure levels, with a high compliance for mandatory disclosure, although the voluntary disclosure level was rather limited. Public business sector companies appear generally to disclose less information than private sector companies. Furthermore, more profitable companies disclose more information than less profitable ones. Results for firm size, gearing and stock activity are mixed.